2007
DOI: 10.1111/j.1365-2826.2007.01537.x
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropeptide Pituitary Adenylate Cyclase‐Activating Polypeptide Exerts Anti‐Apoptotic and Differentiating Effects during Neurogenesis: Focus on Cerebellar Granule Neurones and Embryonic Stem Cells

Abstract: Pituitary adenylate cyclase‐activating polypeptide (PACAP) was originally isolated from ovine hypothalamus on the basis of its hypophysiotrophic activity. It has subsequently been shown that PACAP and its receptors are widely distributed in the central nervous system of adult mammals, indicating that PACAP may act as a neurotransmitter and/or neuromodulator. It has also been found that PACAP and its receptors are expressed in germinative neuroepithelia, suggesting that PACAP could be involved in neurogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…The effects of PACAP on apoptosis have been well studied on neuronal cells such as cerebellar granule cells, PC12 cells, cortical neurons, and in vivo retinal tissue (Delcourt et al 2007;Falluel-Morel et al 2007;Racz et al 2006Racz et al , 2007aRavni et al 2006;Somogyvari-Vigh and Reglodi 2004). However, several studies indicate that PACAP exerts anti-apoptotic effects also in nonneuronal cells.…”
Section: Discussionmentioning
confidence: 97%
“…The effects of PACAP on apoptosis have been well studied on neuronal cells such as cerebellar granule cells, PC12 cells, cortical neurons, and in vivo retinal tissue (Delcourt et al 2007;Falluel-Morel et al 2007;Racz et al 2006Racz et al , 2007aRavni et al 2006;Somogyvari-Vigh and Reglodi 2004). However, several studies indicate that PACAP exerts anti-apoptotic effects also in nonneuronal cells.…”
Section: Discussionmentioning
confidence: 97%
“…The neuroprotective and neurotrophic actions of PACAP were first reported by Arimura et al (1994), and subsequent work from his lab has revealed much about the mechanisms that are involved (Li et al 2005). There is now great interest in PACAP as a possible differentiation factor for embryonic stem (ES) cells that could be used to induce a neuronal phenotype (Cazillis et al 2004;Falluel-Morel et al 2007). LIF is particularly known for its ability to suppress the differentiation of mouse ES cells in culture (Smith et al 1988;Williams et al 1988) but was ineffective for human ES cells, which appear to require different signals to maintain them in a pluripotent state (Dahéron et al 2004;Okita and Yamanaka 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Pituitary adenylate cyclase-activating polypeptide (PACAP) is a member of the growing family of neurotrophic and neuroprotective factors playing important roles during neuronal development and protection against different types of injuries, like cerebellar and cortical development, protection against Parkinson's disease, excitotoxicity, and ischemia (Waschek 2002;Somogyvari-Vigh and Reglodi 2004;Shioda et al 2006;Falluel-Morel et al 2007). PACAP and its receptors are present in the eye (Seki et al 2000a, b;Vereczki et al 2006), and various different effects on inflammatory processes, cytokine production, vascular supply, and circadian functions have already been demonstrated (Nilsson 1994;Jozsa et al 2001;Hannibal and Fahrenkrug 2004;Nakatani et al 2006).…”
Section: Introductionmentioning
confidence: 99%